Increased Load Power With Centralized Control of Multiple Microgrid Resources - Kusmantoro, Adhi (KnE Social Sciences, 2024)
There are many rural areas on remote islands that cannot be reached by electricity sources from the utility grid. However, Indonesia is a country that has an abundant supply of renewable energy. One of the renewable energies that is obtained for free is solar energy sources. Renewable energy has great potential as a source of distributed electricity generation or microgrids. This article proposes a new method for providing large electrical power supplies for rural areas, namely multiple microgrids with a centralized control strategy. The purpose of this method is to provide stability of power supply to the load. In this method, each microgrid has solar panels (SP), batteries, and diesel generators (GD). Multiple microgrids provide power supply to DC loads and AC loads. The centralized controller uses an outseal programmable logic controller (PLC) which functions to regulate the power flow of microgrid 1 (MG1), microgrid 2 (MG2), and microgrid 3 (MG3) to the load alternately. Simulation test results show the performance of a centralized control which is able to provide power supply to the load according to demand or changes in load. Power regulation management for rural areas can be developed for large-scale microgrid systems. Keywords: multiple-microgrid; centralized control; solar panel